Penerapan Data Mining Untuk Pengelompokan Hasil Diagnosa Penyakit Pasien Pengguna BPJS Kesehatan (Studi Kasus Pada Rsud Undata Palu) - Amriana, Amriana; Joefrie, Yuri Yudhaswana; Meidji, Farah Nabila (Fakultas Teknik, Universitas Tadulako, 2018)
This research was conducted to process medical record data in RSUD Undata of central Sulawesi province, for some BPJS Kesehatan insurance member. Medical record contain information about identity and medical history by patientÂ in Hospital or community health center (Puskesmas). Medical records have disease information by patients encoded according to WHO standart. The code is called ICD (International Classification of Disease) and this research use C4.5 Algorithm as Classification method to process patient medical record which then uses address attributes, gender, age and disease diagnosis (ICD-10). Of the five attributes are groupings then processed into group of age, regional and icd. The result of this studi can find patterns of disease tendency that most suffered by people in a region.